Numerical Modeling of Time-Fractional Phase-Change Problems - Azrak, Sura (2025)
A Master of Science thesis in Mathematics by Sura Azrak entitled, “Numerical Modeling of Time-Fractional Phase-Change Problems”, submitted in July 2025. Thesis advisor is Dr. Youssef Belhamadia. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).